Diffraction at a time grating in above-threshold ionization: The influence of the Coulomb potential - Arbo, Diego (2010)
We analyze the photoelectron emission spectrum in atomic above-threshold ionization by a linearly polarized short-laser pulse. Direct electrons can be characterized by both intracycle and intercycle interferences. The former results from the coherent superposition of two different electron trajectories released in the same optical cycle, whereas the latter is the consequence of the superposition of multiple trajectories released in different cycles. In the present article, a semiclassical analytical expression for the complete (both intracycle and intercycle) interference pattern is derived. We show that the recently proposed semiclassical description in terms of a diffraction process at a time grating remains qualitatively unchanged in the presence of the long-range Coulomb potential. The latter causes only a phase shift of the intracycle interference pattern. We verify the predictions of the semiclassical model by comparison with full three-dimensional (3D) time-dependent Schrödinger equation (TDSE) solutions. One key finding is that the subcycle interference structures originating from trajectories launched within a time interval of less than 1 femtosecond should be experimentally observable also in low-resolution spectra for longer multicycle pulses.